2022
DOI: 10.3389/fnut.2022.960409
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between plasma fatty acids in adults with mild, moderate, or severe COVID-19 and the development of post-acute sequelae

Abstract: BackgroundSARS-CoV-2 has infected millions across the globe. Many individuals are left with persistent symptoms, termed post-acute sequelae of COVID-19 (PASC), for months after infection. Hyperinflammation in the acute and convalescent stages has emerged as a risk factor for poor disease outcomes, and this may be exacerbated by dietary inadequacies. Specifically, fatty acids are powerful inflammatory mediators and may have a significant role in COVID-19 disease modulation.ObjectiveThe major objective of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Patients with more depleted levels of γ-linolenic acid (GLA) and eicosapentaenoic acid (EPA) during recovery from acute COVID-19 are more likely to develop Long COVID (393). Depletion of EPA impairs vasodilation, worsens oxidative stress and enhances inflammation, making it a plausible contributor to the pathogenesis of Long COVID (394).…”
Section: Similarities and Differences In Underlying Biologymentioning
confidence: 99%
“…Patients with more depleted levels of γ-linolenic acid (GLA) and eicosapentaenoic acid (EPA) during recovery from acute COVID-19 are more likely to develop Long COVID (393). Depletion of EPA impairs vasodilation, worsens oxidative stress and enhances inflammation, making it a plausible contributor to the pathogenesis of Long COVID (394).…”
Section: Similarities and Differences In Underlying Biologymentioning
confidence: 99%
“…In various clinical studies, GLA adjuvant has been studied as a potential treatment for influenza, tuberculosis, malaria, HIV, schistosomiasis, leishmaniasis, and Hansen’s disease 33 . Also, changes in blood GLA levels have been reported in some diseases 34 . In our search, we found only a few studies that describe the use of GLA for pain 17 , 20 .…”
Section: Discussionmentioning
confidence: 98%
“…Nowadays, particular interest is focused on vascular complications of COVID-19, especially in obese patients [ 45 ]. It was shown that a relatively higher risk of vascular complications and thrombosis occurs in those with elevated levels of palmitate but not unsaturated FAs in the plasma [ 46 ]. Furthermore, a higher risk of thrombosis in COVID-19 patients was attributed to an elevated vWF level [ 47 ].…”
Section: Discussionmentioning
confidence: 99%